Genetic diversity of traditional South American landraces of cassava (Manihot esculenta Crantz): An analysis using microsatellites - Elias, M.; Muhlen, GS; McKey, D; Roa, A.C.; Tohme, Joseph M. (2004)
The extent and structure of the genetic variability of traditional varieties of cassava (Manihot esculenta Crantz) have been little documented, despite considerable evidence for this crop's great varietal diversity in traditional agroecosystems. We used microsatellite markers to assess the genetic structure of traditional landraces of sweet and bitter cassava collected from five South American sites. As reference, we used a sample of 38 accessions from a world collection of cultivated cassava. For a total of 10 loci examined, we found 15 alleles that were not represented in this sample. Ten of these had been previously detected in wild Manihot species. The geographical structure of genetic variability was weak, but the genetic differentiation between bitter and sweet landraces was significant, suggesting that each form had evolved separately after domestication. Our results showed that traditional landraces form an important source of genetic diversity and merit more attention from managers of crop genetic resources.